Analysis the Curriculum of Technology and Islamic Entrepreneurship Based on Local Potential - Islami Fatwa; Siraj Siraj; Abubakar Abubakar; Mulya Afandi; M. Ikram (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
The objective of this research is to analyze and evaluate the implementation of the technology and Islamic entrepreneurship curriculum based on local potential in Vocational High Schools, as well as to identify the impact of this curriculum on the quality of education, student skills, and its relevance to the needs of industry and local communities. This study aims to assess how the integration of technology, Islamic entrepreneurship, and local potential in the curriculum affects students' technical and entrepreneurial skills. Data collection in this study used three techniques: in-depth interviews, participant observation and documentation study. The data analysis technique used is the interactive model which includes: data reduction, data presentation, and conclusion drawing. The research findings show that the curriculum of technology and Islamic entrepreneurship based on local potential in Vocational High Schools contributes significantly to the improvement of students' skills, strengthening the relationship between the education sector and industry, as well as enhancing the welfare of the surrounding community. However, to achieve optimal results, stronger support from the government and industry is required